PENGGUNAAN AUDIO VISUAL PADA PEMBELAJARAN IPS DI SD/MI - Fitri Aulia Rahmah; Ratu Siti Aisyah; Khansa Fakhira Maulidia; Oman Farhurohman (PT. Hasba Edukasi Mandiri, 2025)
This study discusses the use of audio-visual media in Social Studies (IPS) learning at Elementary and Islamic Elementary Schools (SD/MI) as an effort to improve students’ motivation and learning outcomes. Using a qualitative library research approach, this study analyzes relevant scientific journals related to the effectiveness of audio-visual media. The findings show that the use of educational videos, documentaries, and interactive multimedia makes learning more engaging, contextual, and enhances students’ understanding of social concepts. Audio-visual media have also been proven to foster empathy, participation, and creativity in understanding social phenomena. However, several challenges remain, including limited facilities, teachers’ skills, and the integration of media with instructional strategies. Overall, audio-visual media play an essential role in realizing active and meaningful Social Studies learning that aligns with the objectives of the Merdeka Curriculum.